The Relationship of Perceived Digital Competence and Attitude, and Learning Agility in Student Engagement - Nanang Sriyadi; Sofyan; Robi Hendra (Postgraduate, University of Mataram, 2025)
This study explores the relationships between perceived digital competence, attitude towards digital technology, learning agility, and student engagement among 246 junior high school students in Muaro Jambi Regency. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, the research investigates how these variables interact to influence sustainable student engagement in a digitally enriched academic environment. The findings indicate that perceived digital competence significantly influences learning agility (β = 0.70), while its direct impact on student engagement is negligible (β = -0.02). Similarly, attitudes toward digital technology positively predict learning agility (β = 0.70) and moderately affect student engagement (β = 0.34). Learning agility emerges as a critical mediator, significantly contributing to student engagement (β = 0.48). These results emphasize the pivotal role of learning agility in bridging digital competence, attitudes, and engagement in academic contexts. The study underscores the importance of fostering adaptable and motivated learners to enhance engagement and calls for targeted interventions to strengthen students’ digital capabilities and attitudes. Future research should consider broader sample diversity and include additional antecedents to refine the model and enhance its generalizability.